Investigations on Microstructure, Mechanical, Thermal, and Tribological Behavior of Cu-MWCNT Composites Processed by Powder Metallurgy. (26th August 2021) - Stalin, B.; Ravichandran, M.; Karthick, Alagar; Meignanamoorthy, M.; Sudha, G. T.; Karunakaran, S.; Bharani, Murugesan
Abstract : Copper (Cu) metal matrix composite (MMC) was developed with multiwall carbon nanotubes (MWCNT) as reinforcement by using powder metallurgy (PM) technique. The composition of the composites is Cu, Cu-4 wt% MWCNT, Cu-8 wt% MWCNT, and Cu-12 wt% MWCNT. The Cu and MWCNTs were blended for 6 hours in a ball mill and compacted at a 6 ton pressure to form green compacts using a 10 ton hydraulic press. Using a tubular furnace, the heat was applied at 900°C for 1.5 hours to impart strength and integrity to the green compacts. Milled composite blends were studied to analyze its characterization through SEM and EDAX analysis. Characterization studies such as SEM and EDAX confirm the presence and even dispersion of Cu and MWCNT constituents. The relative density, hardness, and ultimate compressive strength have been studied, and a remarkable improvement in properties has been obtained by the inclusion of MWCNTs. The composites reinforced by 8 and 12 wt% MWCNT were recorded with low thermal conductivity than the Cu composite reinforced by 4 wt% MWCNT. A wear study was analyzed using Taguchi technique for determining the effect caused by the wear test parameters and MWCNT content on wear rate. The optimized parameter that contributes minimum wear rate was identified as 12 wt% MWCNT content, 10 N applied load, 2 m/s sliding velocity, and 500 m sliding distance. Based on the obtained results, it could be understood that the produced composites can be utilized for various applications like relay contact springs and switchgear, rotor bars, and bus bars.